OPTIMASI PENEMPATAN DAN KAPASITAS KAPASITOR UNTUK MEMINIMALKAN SUSUT DAYA PADA PENYULANG TABANAN DENGAN MENGGUNAKAN METODE ANT COLONY OPTIMIZATION (ACO) - Arialdi, Fadil; Sari Hartati, Rukmi; Mataram, I Made (Jurnal SPEKTRUM; Vol 6 No 4 (2019): Jurnal SPEKTRUM, 2019)
Electricity is one of the needs of society that must be met, because electricity is very instrumental in helping everyday life, such as lighting, and for the electronic needs. In distributing power to consumers there is a power loss in the distribution system channel. To reduce power loss, it is necessary to install capacitors. This study aims to reduce power losses in Tabanan feeders using the Ant Colony Optimization (ACO) method with 10 attempts using MATLAB. The total power loss before the capacitor is installed is 0.421 MW (6,4%), after the analysis is obtained the placement of the capacitor located on bus 10 with a capacity of 1000 KVAR, can reduce the power loss to 0.145 MW (2,2%)